2018
DOI: 10.1186/s12866-018-1226-4
|View full text |Cite
|
Sign up to set email alerts
|

The microbiota in the intestinal and respiratory tracts of naked mole-rats revealed by high-throughput sequencing

Abstract: BackgroundThe naked mole-rat (NMR, Heterocephalus glaber) is being bred as a novel laboratory animal due to its unique biological characteristics, including longevity, cancer resistance, hypoxia tolerance, and pain insensitivity. It is expected that differences exist between the microbiota of wild NMRs and that of NMRs in an artificial environment. Overall, the effect of environment on changes in the NMR microbiota remains unknown. In an attempt to understand the microbiota composition of NMRs in captivity, va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
(37 reference statements)
1
8
0
Order By: Relevance
“…Whether in normoxia or hypoxia, the gut bacteria of the two predominant phyla of Gansu zokors were Firmicutes and Bacteroidetes; this is consistent with the studies on naked mole-rat, blind mole-rat, and plateau zokors under normoxia ( 29 , 33 , 49 ), indicating that Gansu zokor has the same dominant phylum with other wild subterranean rodents. Moreover, an increased Firmicutes/Bacteroidetes (F-B) ratio under hypoxia conditions of SH44h and MH4w indicates that these two treatments have a higher impact on the gut microbiota; meanwhile, the SH44h and MH4w groups also showed higher F-B ratio than other hypoxia groups of having the equal concentration or time, which is also embodied in the ecological diversity metrics analyses (alpha diversity and beta diversity).…”
Section: Discussionsupporting
confidence: 87%
“…Whether in normoxia or hypoxia, the gut bacteria of the two predominant phyla of Gansu zokors were Firmicutes and Bacteroidetes; this is consistent with the studies on naked mole-rat, blind mole-rat, and plateau zokors under normoxia ( 29 , 33 , 49 ), indicating that Gansu zokor has the same dominant phylum with other wild subterranean rodents. Moreover, an increased Firmicutes/Bacteroidetes (F-B) ratio under hypoxia conditions of SH44h and MH4w indicates that these two treatments have a higher impact on the gut microbiota; meanwhile, the SH44h and MH4w groups also showed higher F-B ratio than other hypoxia groups of having the equal concentration or time, which is also embodied in the ecological diversity metrics analyses (alpha diversity and beta diversity).…”
Section: Discussionsupporting
confidence: 87%
“…The body content of vitamins from the B series including nicotinamide as well as of polyamines and bile acids are strongly influenced by the intestinal microbiota (because bacteria are able to synthesize them), supporting the intriguing, yet-to-be-confirmed hypothesis that (some of) the longevity-associated metabolic alterations found in naked mole-rats actually reflect a particular gut flora [48]. Thus, one species that is highly abundant in the gut from naked mole-rats, Bacillus megaterium [49,50], is also particular efficient in polyamine biosynthesis [51,52]. These results call for an extensive functional characterization of the naked mole-rat microbiota with respect to its possible longevity-conferring properties.…”
Section: Discussionmentioning
confidence: 97%
“…A comparison of the gut bacterial communities between laboratory and wild S. murinus revealed a higher microbial diversity in the latter [ 9 ]. Other studies have revealed the bacterial communities of the gastrointestinal and respiratory tracts of laboratory rats [ 10 ]. However, to the best of our knowledge, there is no literature addressing the composition of the oropharynx bacterial communities of S. murinus or R. norvegicus .…”
Section: Introductionmentioning
confidence: 99%